Reconstructing language curriculum in the digital era: A qualitative study on the role of technology in transforming learning - Wahdini, Lili; Murtini, Murtini; Susandi, Deny Gunawan; Rodiyah, Siti; Sjafei, Irna (Universitas Islam Sultan Agung, 2025)
In the midst of rapid digital transformation, language education faces the urgent need to redesign curricula that align with technological advancements while ensuring inclusivity. This study aims to investigate how technology facilitates the reconstruction of language curricula in urban Indonesian contexts. Employing a qualitative multi-site case study design, data were collected from 15 language teachers across eight schools in South Jakarta and South Tangerang between August and October 2024 through semi-structured interviews, classroom observations, and document analysis. Thematic analysis revealed three major findings: (1) technological adaptation varied by region, with South Jakarta schools integrating advanced tools such as AI-powered applications, while South Tangerang relied on basic platforms due to infrastructural constraints; (2) pedagogical shifts toward learner-centered approaches were more evident in well-resourced schools, supported by collaborative digital tools; and (3) inclusivity efforts, including smartphone-based activities and bilingual resources, were hindered by socioeconomic disparities and unstable internet access. The study concludes that while technology holds transformative potential for language education, its impact is constrained by resource inequities, highlighting the need for targeted teacher training and equitable infrastructure investment. These findings contribute to the limited Southeast Asian literature on technology-enhanced curriculum design and offer practical implications for policymakers and educators in developing contexts.